Method for the production of a skin care powder, skin care powder and use thereof
Patent Information
- Application Number
- CN202611382806.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-09
AI Technical Summary
当粉体涂抹于干燥皮肤区域时,皮肤表层缺少游离液态介质,裸露的活性物不具备脂质亲和结构,无法穿透角质层屏障,绝大部分活性物会随粉体摩擦、脱落流失,实际透皮利用率极低
[0016]相对于现有技术而言,本申请提供的皮肤护理粉体的制备方法中,利用固态脂质作为载体包封和递送功效活性物,延缓活性物的氧化失活;涂抹于皮肤后,在人体体温和摩擦剪切力的双重作用下,触发剂型转化,固态脂质纳米粒的脂质晶格快速软化、溶胀破裂,原位形成脂质乳液,活性物脱离粉体的吸附,依靠与角质层同源的脂质结构渗透进入皮肤角质层,提升活性物透皮吸收率。相较于传统干粉直混体系,本申请的皮肤护理粉体无需将活性物裸露吸附在粉体表面,成品储存稳定性优异,无分层、局部活性偏析等问题。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This application relates to the field of cosmetic powder technology, and in particular to a method for preparing skin care powder, the skin care powder prepared by the method, and its application. Background Technology
[0002] Currently, skin care powders on the market include talcum powder, body care powder, and brightening and nourishing loose powder. Most of them use mineral powders such as mica, silica, modified starch, and boron nitride or natural polymer powders as the matrix. In order to give the powder skin care effects, powdered active ingredients are added to the powder matrix using a dry powder direct mixing process.
[0003] However, the aforementioned dry powder system is a simple solid-solid mixture. The matrix powders, such as silica and modified mica, have a large specific surface area and extremely strong surface adsorption capacity, firmly binding the active ingredient molecules to the surface of the powder particles and the spaces between them. When the powder is applied to dry skin areas, the skin surface lacks a free liquid medium. The exposed active ingredients lack lipid affinity structures and cannot penetrate the stratum corneum barrier. Most of the active ingredients are lost through friction and shedding, resulting in extremely low actual transdermal utilization. Furthermore, to achieve oil control and a matte, dry finish, existing powder formulations often contain a large proportion of highly adsorbent powders, which quickly absorb and deplete the skin's own sebum. When active ingredients are in a dry, low-oil environment for extended periods, they are prone to oxidation and decomposition, yellowing and discoloration, and exacerbate dryness, tightness, fine lines, and makeup caking and peeling. Summary of the Invention
[0004] This application provides a method for preparing skin care powder, the skin care powder prepared by the method and its application, which can achieve the effects of controllable spontaneous transformation of powder formulation, long-lasting and stable activity, and deep transdermal skin care.
[0005] In a first aspect, embodiments of this application provide a method for preparing skin care powder, comprising the following steps: preparing a nano-lipid carrier emulsion loaded with active ingredients: heating and melting solid lipids, liquid lipids, and active ingredients to obtain an oil phase; dissolving an emulsifier and a freeze-drying protectant in water to obtain an aqueous phase; mixing the oil phase and the aqueous phase, shearing and emulsifying, and then placing the mixture in an ice bath for freeze-drying phase change to obtain a nano-lipid carrier emulsion loaded with active ingredients; preparing a wet powder slurry: mixing and homogenizing the nano-lipid carrier emulsion loaded with active ingredients with a powder matrix to obtain a wet powder slurry; vacuum freeze-drying: subjecting the wet powder slurry to vacuum freeze-drying and pulverizing to obtain a skin care powder with a spontaneous dosage form conversion function.
[0006] In the oil phase, the solid lipid is glycerol stearate, the liquid lipid is squalane, the active ingredient has an octanol-water partition coefficient LogP greater than or equal to 3.0, and a pH value of 5.0~7.0; and the mass ratio of solid lipid, liquid lipid and active ingredient is (4~8):(15~23):1; the emulsifier is selected from one or more of highly hydrophilic nonionic surfactants with an apparent HLB value of 20~31, and the mass of the emulsifier is 0.2~0.3 times the total mass of the oil phase; the total mass of the powder matrix is 5~7.5 times the total mass of the oil phase, and based on the total mass of the powder matrix, the powder matrix includes 40%~45% lauroyl lysine-coated synthetic fluorophlogopite and 15%~20% porous silica.
[0007] According to the embodiments of the first aspect of this application, the active ingredients include one or more of astaxanthin, ethyl ferulic acid, psoralen, ascorbyl tetraisopalmitate, β-carotene, tocopherol, retinol, retinyl palmitate, ceramide, phytosterol, and bisabolol.
[0008] According to an embodiment of the first aspect of this application, the emulsifier is selected from one or more of poloxamer 188, poloxamer 238, poloxamer 338, and poloxamer 407.
[0009] According to an embodiment of the first aspect of this application, the freeze-drying protectant includes trehalose and mannitol, and the mass of the freeze-drying protectant is 0.1 to 0.2 times the total mass of the oil phase.
[0010] According to an embodiment of the first aspect of this application, the mass of water is 1 to 2 times the total mass of the oil phase.
[0011] According to the embodiments of the first aspect of this application, the powder matrix further includes one or more of the following: unmodified synthetic fluorophlogopite, starch derivatives, boron nitride, inorganic functional composite powder, silica powder, metal oxide powder, inorganic phosphate powder, organosilicon resin microspheres, and organic polymer microspheres.
[0012] According to an embodiment of the first aspect of this application, in the step of preparing a nanolipid carrier emulsion loaded with active ingredients, the shearing speed of the shear emulsification is 10,000 rpm to 14,000 rpm, and the time is 4 to 6 minutes.
[0013] According to the embodiments of the first aspect of this application, the step of preparing the powder wet slurry is carried out at 10~15°C; and / or, before vacuum freeze-drying the powder wet slurry, the powder wet slurry is pre-frozen at -50°C~-40°C for 2 to 4 hours.
[0014] Secondly, embodiments of this application provide a skin care powder, prepared according to any method in the embodiments of the first aspect of this application.
[0015] Thirdly, embodiments of this application provide an application of the skin care powder from the second aspect of this application in the preparation of powder cosmetics.
[0016] Compared to existing technologies, the skin care powder preparation method provided in this application utilizes solid lipids as a carrier to encapsulate and deliver active ingredients, delaying their oxidative deactivation. Upon application to the skin, under the combined effects of body temperature and frictional shear force, a dosage form conversion is triggered. The lipid lattice of the solid lipid nanoparticles rapidly softens, swells, and ruptures, forming a lipid emulsion in situ. The active ingredients detach from the powder's adsorption and penetrate the stratum corneum through their lipid structure, which is homologous to the stratum corneum, thus enhancing the transdermal absorption rate of the active ingredients. Compared to traditional dry powder direct-mixing systems, the skin care powder of this application does not require the active ingredients to be exposed and adsorbed on the powder surface. The finished product exhibits excellent storage stability and exhibits no issues such as stratification or localized active ingredient segregation. Detailed Implementation
[0017] To better understand the above-mentioned objectives, features, and advantages of this disclosure, the solutions disclosed herein will be further described below. It should be noted that, unless otherwise specified, the embodiments and features described herein can be combined with each other.
[0018] Numerous specific details are set forth in the following description in order to provide a full understanding of this disclosure, but this disclosure may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only one embodiment of this disclosure, and not all embodiments.
[0019] In a first aspect, embodiments of this application provide a method for preparing skin care powder, comprising the following steps: preparing a nano-lipid carrier emulsion loaded with active ingredients: heating and melting solid lipids, liquid lipids, and active ingredients to obtain an oil phase; dissolving an emulsifier and a freeze-drying protectant in water to obtain an aqueous phase; mixing the oil phase and the aqueous phase, shearing and emulsifying, and then placing the mixture in an ice bath for freeze-drying phase change to obtain a nano-lipid carrier emulsion loaded with active ingredients; preparing a wet powder slurry: mixing and homogenizing the nano-lipid carrier emulsion loaded with active ingredients with a powder matrix to obtain a wet powder slurry; vacuum freeze-drying: subjecting the wet powder slurry to vacuum freeze-drying and pulverizing to obtain a skin care powder with a spontaneous dosage form conversion function.
[0020] In the oil phase, the solid lipid is glycerol stearate, the liquid lipid is squalane, the active ingredient has an octanol-water partition coefficient LogP greater than or equal to 3.0, and a pH value of 5.0~7.0; and the mass ratio of solid lipid, liquid lipid and active ingredient is (4~8):(15~23):1; the emulsifier is selected from one or more of highly hydrophilic nonionic surfactants with an apparent HLB value of 20~31, and the mass of the emulsifier is 0.2~0.3 times the total mass of the oil phase; the total mass of the powder matrix is 5~7.5 times the total mass of the oil phase, and based on the total mass of the powder matrix, the powder matrix includes 40%~45% lauroyl lysine-coated synthetic fluorophlogopite and 15%~20% porous silica.
[0021] The method for preparing skin care powder provided in this application achieves the effects of controllable spontaneous transformation of powder formulation, long-lasting and stable activity, and deep transdermal skin care through the synergistic interaction of a specific lipid compound system, a highly hydrophilic emulsification system, active ingredients with limited physicochemical parameters, and a specific compound powder matrix.
[0022] Specifically, in the step of preparing the nanolipid carrier emulsion loaded with active ingredients, solid lipids, liquid lipids, and active ingredients in a specific ratio are mixed and heated to a molten state to form a homogeneous oil phase. A highly hydrophilic emulsifier and a lyophilization protectant are added to water to obtain a homogeneous aqueous phase. The prepared oil phase and aqueous phase are mixed, and a high-speed shear emulsification process is used to achieve uniform fusion of the two phases, constructing a nascent lipid vesicle structure. After emulsification, the mixture is placed in an ice bath for a freeze-phase change treatment. Rapid low-temperature induction promotes the regularization and formation of the lipid lattice, ultimately yielding a structurally stable nanolipid carrier emulsion loaded with active ingredients.
[0023] In the step of preparing the wet powder slurry, the nanolipid carrier emulsion loaded with active ingredients from the above steps is mixed with the powder matrix and thoroughly homogenized and dispersed using a homogenizing stirring process. The high-speed shearing and impact forces during homogenization ensure that the lipid vesicles in the nanolipid carrier emulsion are uniformly dispersed and embedded within the interlamellar gaps and porous microporous structure of the powder matrix, preventing lipid vesicle aggregation, floating, or demulsification, thus forming a tightly bonded composite structure between the lipid carrier and the powder matrix.
[0024] In the step of preparing skin care powder with spontaneous dosage form conversion function, the wet slurry of powder prepared in the above steps is subjected to vacuum freeze-drying treatment. The water used for preparation in the system is completely removed by low temperature vacuum freeze-drying mode, so as to avoid the damage of high temperature process to lipid carrier structure and active ingredients, and to preserve the microstructure and bioactivity of nano lipid vesicles. After freeze-drying, appropriate pulverization and granulation treatment can be carried out to finally obtain skin care powder with spontaneous dosage form conversion function.
[0025] In order to achieve the spontaneous conversion function of the nanoliposome carrier and the stability during preparation and storage, the composition of the formulation system was purposefully selected in this application.
[0026] First, this application selected glyceryl stearate and squalane from a wide range of solid and liquid lipids, and combined them in a specific ratio range as the basic framework of the nanolipid carrier. This not only allows the nanolipid to successfully form a disordered defect lattice to accommodate active ingredients, but more importantly, it can obtain a lipid mixture with an apparent melting range of 32-35°C. This locks the physical softening point of the nanolipid carrier at 32-35°C, reaching the phase transition critical point at skin temperature, and achieving the purpose of triggering dosage form conversion and active ingredient release using body temperature and frictional shear force.
[0027] Secondly, in the implementation of this application, ensuring the stability of the nanolipid carrier emulsion and preventing demulsification and flocculation of nanolipid particles during the preparation of the nanolipid carrier emulsion loaded with active ingredients and the mixing of the nanolipid carrier emulsion with a large amount of powder matrix to prepare the powder wet slurry is a challenging process. This application effectively solves the above technical problems by purposefully selecting emulsifiers, adjusting the LogP and pH value of the active ingredients, and strictly controlling the composition of the main powder in the powder matrix. The mechanism is as follows: First, regarding the type of emulsifier, this application did not select emulsifiers with HLB values of 8 to 18 commonly used in the field for oil-in-water emulsions (such as Tween 80, with an HLB value of around 15). Instead, it selected highly hydrophilic nonionic surfactants with apparent HLB values of 20 to 31. The role of this type of surfactant in this application is not simply to meet the emulsification requirements, but to build strong steric hindrance based on ultra-long hydrophilic chains on the basis of emulsification. In the subsequent mixing of a large amount of powder matrix and freeze-drying process, it plays a role in resisting powder adsorption, ice crystal stress, and particle agglomeration.
[0028] Second, the active ingredient in this application has an octanol-water partition coefficient LogP greater than or equal to 3.0, a pH value of 5.0 to 7.0, and a ratio of its amount with glycerol stearate and squalane within a defined range. The active ingredient has strong lipophilicity and can be completely co-soluble with glycerol stearate and squalane, and can be smoothly encapsulated into the core of the nanolipid carrier. In subsequent preparation processes, it will not cause hydrolysis of glycerol stearate or demulsification of the nanolipid carrier, and it is not easy for the active ingredient to be free in the aqueous phase, resulting in a decrease in the encapsulation rate.
[0029] Third, the powder matrix in this application includes at least 40% to 45% lauroyl lysine-coated synthetic fluorophlogopite and 15% to 20% porous silica. The lauroyl lysine-modified synthetic fluorophlogopite improves the powder's dispersibility and lubrication, reducing the risk of demulsification of the nanolipid carrier emulsion during the mixing stage. The porous silica anchors the nanolipid carrier particles through its porous structure, preventing lipid particle aggregation during freeze-drying and enabling controlled release of active ingredients during application. The combination of lauroyl powder and spherical porous powder forms a three-dimensional loose framework, regulating the friction threshold during skin application and synergistically achieving softening of nanolipid particles and release of active ingredients induced by body temperature and frictional pressure.
[0030] Simultaneously, the internal composition ratio of the oil phase was adjusted to (4~8):(15~23):1. This ratio range balances the structural stability, phase transition sensitivity, and active ingredient loading of lipid vesicles, ensuring that the nanolipid carrier remains structurally intact, unbroken, and free of active ingredient release during dry storage, while also ensuring rapid swelling and rupture of the vesicles to release the active ingredients after application to the skin, thus balancing product storage stability and skincare efficacy release efficiency. The emulsifier was added at 0.2~0.3 times the total mass of the oil phase. This dosage range helps to balance emulsification effect, vesicle structural stability, and the final skin feel of the powder, avoiding excessive emulsifier leading to stickiness and reduced oil control effect, or insufficient emulsifier leading to vesicle structural instability. The total mass of the powder matrix was adjusted to 5~7.5 times the total mass of the oil phase. By loading a small amount of lipid vesicles onto the powder matrix at a high proportion, it helps to retain the dry, matte skin feel of the powder and reduce the greasiness caused by the lipid system.
[0031] For example, the octanol-water partition coefficient LogP of the active ingredient can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or any value between any two of the above. Preferably, the octanol-water partition coefficient LogP of the active ingredient can be 3, 4, 5, 6, 7, 8, or any value between any two of the above, to achieve easier penetration of the stratum corneum and lower irritation. The octanol-water partition coefficient LogP of the active ingredient is also called the lipid-water partition coefficient (octanol is a model solvent for simulating biological lipid phases) and is used to characterize the inherent lipophilicity of the active ingredient molecule. The higher the LogP (Log-P ratio), the stronger the lipophilicity of the active ingredient molecule. The LogP of an active ingredient can be determined using the OECD TG 107 shake-flask method or the OECD TG 123 slow-stirring method, as specified in the OECD Chemicals Testing Guidelines. This parameter is often included in the information on commercially available active ingredient raw materials or can be obtained from the supplier.
[0032] For example, the mass ratio of solid lipids, liquid lipids and active ingredients can be 4:15:1, 4:18:1, 4:23:1, 6:16:1, 6:19:1, 6:21:1, 8:15:1, 8:23:1 or any range between the two above.
[0033] For example, the apparent HLB value of the emulsifier is 20, 23, 25, 28, 31 or a range between any two of the above.
[0034] For example, the ratio of the powder matrix to the total mass of the oil phase is 5.0, 5.5, 6.0, 6.5, 7.0, 7.5 or any two of the above.
[0035] For example, the pH value of the active ingredient is 5.0, 5.5, 6.0, 6.5, 7.0 or any two of the above.
[0036] For example, the mass percentage of fluorophlogopite coated with lauroyl lysine is 40%, 41%, 42%, 43%, 44%, 45%, or any value between the two mentioned above.
[0037] For example, the mass percentage of porous silica is 15%, 16%, 17%, 18%, 19%, 20%, or any value between the two mentioned above.
[0038] In some embodiments, the active ingredient includes one or more of astaxanthin, ethyl ferulic acid, psoralen, ascorbyl tetraisopalmitate, β-carotene, tocopherol, retinol, retinyl palmitate, ceramide, phytosterol, and bisabolol.
[0039] The aforementioned active ingredients possess lipophilic properties and a high n-octanol-water partition coefficient, making them soluble within the lipid carrier framework constructed from glyceryl stearate and squalane. Among them, astaxanthin, β-carotene, and tocopherol exhibit excellent antioxidant capabilities, scavenging free radicals and delaying skin oxidative aging; ethyl ferulic acid and tetraisopalmitate are fat-soluble whitening and brightening ingredients with far superior stability compared to water-soluble vitamin derivatives, improving dull skin tone and evening out skin tone; bakuchiol possesses antibacterial, oil-controlling, and soothing repairing effects; retinol and retinyl palmitate promote skin metabolism, refine skin texture, and improve fine lines; their fat-soluble structure allows for efficient transdermal penetration via lipid carriers; ceramides and phytosterols repair the skin barrier, replenish skin lipids, and alleviate the dryness and tightness issues associated with traditional powders; bisabolol possesses gentle soothing properties, reducing the irritation of powders to sensitive skin. The above-mentioned active ingredients can be added alone or in combination, giving the skin care powder of this application multiple skin care effects such as anti-oxidation, brightening and whitening, anti-aging and fine line reduction, barrier repair, and soothing and stabilizing.
[0040] In some embodiments, the emulsifier is selected from one or more of poloxamer 188, poloxamer 238, poloxamer 338, and poloxamer 407.
[0041] The aforementioned poloxamer series raw materials are all polyoxyethylene-polyoxypropylene block copolymers, belonging to the ultra-high hydrophilic nonionic surfactants with apparent HLB values of 20-31 as defined in this application. These various emulsifiers can be added individually or in combination.
[0042] In some embodiments, the freeze-drying protectant includes trehalose and mannitol, and the mass of the freeze-drying protectant is 0.1 to 0.2 times the total mass of the oil phase.
[0043] The freeze-drying protectant used in this application is a combination of trehalose and mannitol. Vacuum freeze-drying is employed to remove moisture from the system. During the freeze-drying process, which involves the formation of ice crystals and the sublimation of water, the nanolipid vesicles are susceptible to ice crystal rupture, structural compression, and interfacial stress, leading to problems such as vesicle rupture, lipid aggregation, and leakage of active ingredients. Simultaneously, the dried powder is prone to defects such as collapse, caking, and decreased flowability. To address these drawbacks of the freeze-drying process, this application uses a combination of trehalose and mannitol as the freeze-drying protectant system, which can achieve a synergistic protective effect. Trehalose is a typical moisturizing and protective sugar that can form a dense protective film at the interface of nanolipid vesicles, replacing water molecules to maintain the interfacial tension and spatial structure of the lipid membrane, preventing the lipid membrane from collapsing and breaking during freeze-drying, and helping to preserve the complete microstructure of the vesicles. Mannitol is a small molecule sugar alcohol with excellent crystallinity. It can build a uniform and loose framework structure during freeze-drying, improve the porosity and loose flowability of the freeze-dried product, prevent powder from caking and agglomerating, and further help stabilize the vesicle morphology and inhibit the aggregation and fusion of lipid particles.
[0044] Meanwhile, this application adjusts the overall dosage of the freeze-drying protectant to 0.1 to 0.2 times the total mass of the oil phase. This not only fully utilizes the technical effects of freeze-drying to protect the shape and prevent agglomeration, which is beneficial for the fine and loose powder and the complete vesicle structure after freeze-drying, but also avoids defects such as excessive protectant leading to powder moisture absorption, sticky feel, and reduced matte oil control effect. Ultimately, this achieves a stable nanolipid carrier structure, excellent powder forming effect, and a good skin feel when using the product.
[0045] In some embodiments, the mass of water is 1 to 2 times the total mass of the oil phase.
[0046] In nanolipid carrier emulsion molding systems, the amount of aqueous phase affects the degree of emulsification and dispersion, vesicle particle size uniformity, and overall emulsion stability. When the amount of water is within the above-mentioned limited range, the oil phase lipid components can be fully and uniformly dispersed in the aqueous phase. Combined with high-speed shearing technology, large-sized lipid aggregates can be broken up, which is conducive to promoting the formation of nanolipid vesicles with uniform particle size and excellent dispersibility. At the same time, it can reduce the defects caused by excessive aqueous phase, such as sparse lipid vesicle concentration, decreased efficiency of subsequent wet mixing and powder loading, disordered pore structure of freeze-drying molding, and poor powder looseness.
[0047] For example, the mass of water relative to the total mass of the oil phase is 1, 1.2, 1.5, 1.8, 2, or any value between two of the above. In some embodiments, the powder matrix further includes one or more of the following: unmodified synthetic fluorophlogopite, starch derivatives, boron nitride, inorganic functional composite powder, silica powder, metal oxide powder, inorganic phosphate powder, organosilicon resin microspheres, and organic polymer microspheres.
[0048] In addition to the limited lauroyl lysine-coated synthetic fluorophlogopite and porous silica, the powder matrix of this application embodiment can also be compounded with a variety of functional auxiliary powders. In this application embodiment, modified flaky mica and porous silica are used as skeleton powders to ensure the stability of the system and the formulation conversion performance. On this basis, the above-mentioned auxiliary powders can be compounded to further optimize the microstructure of the powder, the feel on the skin, the optical soft-focus effect and the storage stability of the finished product.
[0049] Among them, unmodified synthetic fluorophlogopite and other layered silicate mineral powders possess excellent sheet-like spreadability and skin-like adhesion, which can further improve the smoothness and uniform spreading effect of the powder, and optimize the uniformity of powder film formation; hydrophobically modified starch derivatives are preferred, which can further improve the anti-caking performance and oil control uniformity of the powder, improve the loose flowability of the powder, and avoid the problem of powder moisture absorption and caking; boron nitride has a silky smooth skin feel and excellent thermal conductivity and smoothness, which can improve the high-end matte soft-focus texture of the powder, while improving the pressure resistance stability of the powder; silica powder and inorganic functional composites Powders and inorganic phosphate powders possess rich porous structures and excellent adsorption properties, which can help anchor trace lipid particles, further improving the storage stability and formulation uniformity of the finished product. Metal oxide powders can impart a natural soft-focus and brightening effect to the powder, softening skin texture and dullness. Organosilicon resin microspheres and organic polymer microspheres have excellent rolling lubrication properties, which can reduce the friction of powder application, improve the lightweight and skin-adhering user experience, and regulate the pore structure of the powder, assisting in achieving a spontaneous formulation conversion effect triggered by body temperature and friction. The above-mentioned auxiliary powders can be added individually or in combination according to the product's skin feel requirements and efficacy positioning.
[0050] In some embodiments, in the step of preparing the nanolipid carrier emulsion loaded with active ingredients, the shearing speed of the shear emulsification is 10,000 rpm to 14,000 rpm, and the time is 4 to 6 minutes.
[0051] High-speed shear emulsification is a crucial step in constructing uniformly sized and structurally stable nanolipid vesicles. The rotation speed and duration significantly affect the degree of emulsification and fusion between the oil and aqueous phases, the uniformity of vesicle particle size distribution, and the overall stability of the emulsion. This application, through extensive process testing, has verified that limiting the shear speed to the range of 10,000 rpm to 14,000 rpm provides sufficient shear breaking force and turbulent mixing force, rapidly breaking down and refining large oil phase droplets. This allows for thorough adhesion and bonding between the lipid raw materials and the emulsifier, promoting the rapid formation of a well-defined nanoscale vesicle structure. Combined with a shearing duration of 4 to 6 minutes, this facilitates a complete emulsification reaction, ensuring uniform assembly of the lipid components, active ingredients, and emulsifier.
[0052] For example, the shearing speed for shear emulsification is 10,000 rpm, 11,000 rpm, 12,000 rpm, 13,000 rpm, 14,000 rpm or any two of the above; the shearing time is 4 minutes, 5 minutes, 6 minutes or any two of the above.
[0053] In some embodiments, the step of preparing the wet powder slurry is carried out at 10~15°C; and / or, before vacuum freeze-drying the wet powder slurry, the wet powder slurry is pre-frozen at -50°C~-40°C for 2 to 4 hours.
[0054] In the process of homogenizing nanolipid carrier emulsions with powder matrix, ambient temperature is an important condition for maintaining the stability of vesicle structure and avoiding lipid phase transition instability. The embodiments of this application limit the homogenization environment to 10-15°C, which can improve the structural rigidity of nanolipid vesicles and enable them to maintain their morphology integrity during strong homogenization with a high proportion of powder matrix, thus providing a uniform and stable precursor structure for subsequent freeze-drying molding.
[0055] Furthermore, this application specifies a low-temperature pre-freezing process before freeze-drying, in which the wet slurry is pre-frozen at an ultra-low temperature of -50℃ to -40℃ for 2 to 4 hours. This allows the moisture inside the wet slurry to quickly and uniformly form fine and regular ice crystals, avoiding the large ice crystals that pierce lipid vesicles and compress and damage the loose framework of the powder caused by conventional slow freezing. The pre-freezing process can fix the microscopic composite structure of the wet powder slurry, maintain the intercalation state of nano-lipid vesicles in the powder matrix, and inhibit the migration, aggregation, and stratification of lipid particles during freeze-drying. At the same time, the regular and fine ice crystals can form a uniform and loose porous structure after vacuum sublimation, further improving the loose flowability, fineness, and smoothness of the finished powder.
[0056] For example, the ambient temperature for preparing the wet slurry is 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, or any two of the above values; for example, the pre-freezing temperature is -50°C, -48°C, -46°C, -44°C, -42°C, -40°C, or any two of the above values; for example, the pre-freezing time is 2h, 2.5h, 3h, 3.5h, 4h, or any two of the above values.
[0057] Secondly, embodiments of this application provide a skin care powder with spontaneous dosage form conversion function, which is prepared by any of the methods in some embodiments.
[0058] This application embodiment prepares a skin care powder with spontaneous dosage form conversion function using the aforementioned preparation method. Compared to traditional mechanically direct-mixed skin care powders, this application embodiment utilizes solid lipid nanoparticles as a carrier to encapsulate and deliver active ingredients, delaying the oxidative inactivation of the active ingredients. After application to the skin, under the dual action of body temperature and frictional shear force, dosage form conversion is triggered. The lipid lattice of the solid lipid nanoparticles rapidly softens, swells, and ruptures, forming a lipid emulsion in situ. The active ingredients detach from the powder adsorption and penetrate into the stratum corneum of the skin through lipid structures homologous to the stratum corneum, improving the transdermal absorption rate of the active ingredients. Compared to traditional dry powder direct-mixing systems, the skin care powder of this application does not require the active ingredients to be exposed and adsorbed on the powder surface, resulting in excellent storage stability of the finished product without problems such as stratification or localized active ingredient segregation.
[0059] Thirdly, embodiments of this application provide the application of a skin care powder with spontaneous dosage form conversion function, as described in the second aspect of this application, in the preparation of powder cosmetics.
[0060] The skin care powder prepared in this application possesses both excellent basic powder performance and unique thermo-responsive formulation transformation skin care function. Under normal conditions, this powder exhibits excellent powder characteristics such as fine and loose texture, good fluidity, smooth spread, and matte soft-focus finish, which can meet the basic makeup and skin care needs of powder cosmetics, including oil control, skin evenness, texture modification, soft-focus brightening, and makeup setting and long-lasting effect. At the same time, relying on its unique thermo- and friction-responsive spontaneous transformation mechanism, it can achieve intelligent transformation from powder to lipid emulsion on the skin surface, releasing multiple skin care activities such as anti-oxidation, whitening and brightening, barrier repair, and soothing and stabilizing effects in a long-lasting and stable manner.
[0061] Based on the aforementioned comprehensive advantages, the skincare powder of this application can be widely used in various powder cosmetic systems. Specifically, it can be used to prepare a variety of product categories, such as skincare loose powder, setting powder, facial brightening powder, body skincare powder, oil-controlling body powder, pre-makeup skincare powder, and makeup skincare powder. It can meet the development needs of daily skincare powder products for gentle repair and long-lasting skincare, as well as the composite functional needs of makeup powder products for setting makeup, soft-focus correction, and skincare while setting makeup. This broadens the formulation development ideas and product application boundaries of functional powder cosmetics.
[0062] Example The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0063] Examples 1-5 Examples 1-5 provide a method for preparing a skin care powder with spontaneous dosage form conversion function, comprising the following steps: Preparation of active ingredient-loaded nanolipid carrier emulsion: Solid lipids, liquid lipids and active ingredients are heated and melted to obtain an oil phase; emulsifiers and lyophilization protectants are dissolved in water to obtain an aqueous phase; the oil phase and aqueous phase are mixed, sheared and emulsified, and then placed in an ice bath for freezing phase change to obtain an active ingredient-loaded nanolipid carrier emulsion; Preparation of wet powder slurry: Mix and homogenize the nano-lipid carrier emulsion loaded with active ingredients with the powder matrix to obtain wet powder slurry; Vacuum freeze-drying: Vacuum freeze-drying and pulverizing of wet powder slurry yields skin care powder with spontaneous dosage form conversion function; in, In the oil phase, the solid lipid is glycerol stearate, the liquid lipid is squalane, the active ingredient has an octanol-water partition coefficient LogP greater than or equal to 3.0, and a pH value of 5.0~7.0; and the mass ratio of solid lipid, liquid lipid and active ingredient is (4~8):(15~23):1; The emulsifier is selected from one or more highly hydrophilic nonionic surfactants with an apparent HLB value of 20 to 31, and the mass of the emulsifier is 0.2 to 0.3 times the total mass of the oil phase. The total mass of the powder matrix is 5 to 7.5 times the total mass of the oil phase. Based on the total mass of the powder matrix, the powder matrix includes 40% to 45% lauroyl lysine-coated synthetic fluorophlogopite and 15% to 20% porous silica.
[0064] The specific process parameters are as follows: shear emulsification speed 12000rpm, shearing time 5min; wet slurry homogenization temperature 12℃; pre-freezing temperature -45℃, pre-freezing time 3h; vacuum freeze drying until the system moisture is completely removed.
[0065] The formulations of the nanolipid carrier emulsions loaded with active ingredients in Examples 1-5 are shown in Table 1, and the formulations of the powder matrix in Examples 1-5 are shown in Table 2.
[0066] Comparative Examples 1-10 The formulations of the nanolipid carrier emulsions loaded with active ingredients for Comparative Examples 1 to 10 are shown in Table 1, and the formulations of the powder matrix for Comparative Examples 1 to 10 are shown in Table 2.
[0067] The content of each component was adjusted according to Tables 1 and 2 to prepare skin care powders for Comparative Examples 1 to 10. The preparation process of the skin care powders for Comparative Examples 1 to 10 was the same as that for Example 1.
[0068] Table 1. Formulation of nanolipid carrier emulsions loaded with active ingredients
[0069]
[0070]
[0071] Table 2 Powder matrix formulation
[0072]
[0073] Performance testing: 1. Testing and Evaluation Methods This application uses indicators such as preparation process stability, active ingredient encapsulation efficiency, spontaneous conversion function of dosage form, and storage stability under multiple temperature gradients to conduct parallel comparative tests on each example and comparative example.
[0074] (1) Stability of the preparation process: During the preparation of nanolipid carrier emulsion loaded with active ingredients and the preparation of powder wet slurry by mixing nanolipid carrier emulsion with powder matrix, visually observe whether the emulsion breaks down, flocculates or other abnormal phenomena occur.
[0075] (2) Encapsulation efficiency of active ingredient: This application employs ultrafiltration centrifugation combined with high-performance liquid chromatography (HPLC) to quantitatively characterize the encapsulation efficiency of nanolipid vesicles, verifying the technical effect of effectively encapsulating the active ingredients within the nanolipid carrier system. Considering that the strong physical adsorption of the porous matrix in the final powder product would severely interfere with the accuracy of the test results, this test is specifically conducted on the nanolipid carrier slurry stage (i.e., the precursor liquid phase before mixing with the skin-friendly composite powder matrix). The specific test procedure is as follows: Step 1: Extraction and quantification of free active ingredients Accurately transfer an appropriate amount (e.g., 1.0 mL) of the prepared nanolipid carrier slurry and place it in the upper test chamber of an ultrafiltration centrifuge tube with a molecular weight cutoff (MWCO) of 30 kDa. Place the ultrafiltration centrifuge tube in a refrigerated centrifuge at 4°C and centrifuge at 4000 rpm for 20 minutes; the low temperature control is intended to prevent the solid lipid skeleton from melting and breaking due to heat generated by high-speed centrifugation. After centrifugation, collect the ultrafiltrate in the lower centrifuge tube, add a suitable organic extraction solvent (such as methanol or acetonitrile) to make up to the volume, and filter through a 0.22 μm microporous membrane to obtain the free active ingredient test solution. Use high-performance liquid chromatography (HPLC) to determine the peak area of the active ingredient at its specific characteristic wavelength, and substitute it into the standard curve to calculate the absolute mass of the unencapsulated free active ingredient in the system, denoted as W_free.
[0076] Step 2: Demulsification and determination of total active ingredient content Separately, accurately transfer an equal volume (e.g., 1.0 mL) of the same batch of nanolipocarrier slurry as in step one into a stoppered volumetric flask, and add sufficient amount of demulsification extraction solvent (such as isopropanol or other strong organic solvents). Place the flask in a constant temperature water bath at 55℃–60℃ and sonicate for 30 minutes. The continuous heating and ultrasonic cavitation completely destroy the physical crystalline framework of the lipid vesicles, causing complete demulsification and promoting 100% release of the encapsulated active ingredients into the solvent. After cooling to room temperature, make up to volume and mix well. Filter through a 0.22 μm microporous membrane to obtain the total active ingredient test solution. Analyze the total absolute mass of the active ingredients contained in this volume of slurry using HPLC, and denoted as W_total.
[0077] Step 3: Calculation of Encapsulation Ratio Based on the precise HPLC quantification of the total active ingredient mass and the free active ingredient mass, the encapsulation efficiency of the nanolipid vesicles prepared in this application was calculated. The encapsulation efficiency calculation formula is as follows:
[0078] (3) Spontaneous conversion function of dosage form: Apply the powder to the skin of the forearm at room temperature. Under the action of body temperature and frictional shear force of circular application, observe whether the powder can spontaneously transform from solid powder to lipid emulsion at skin temperature to determine whether it has the spontaneous conversion function of dosage form.
[0079] (4) Storage stability test: The powders obtained from each example and comparative example were sealed and stored at -18℃, -5℃, 4℃, 25℃ and 48℃ for 3 months, respectively. The powders were observed regularly for abnormal phenomena such as layering, discoloration, agglomeration and oil release to determine the stability of the system. No storage stability test was conducted for groups that experienced severe demulsification and flocculation during the preparation process.
[0080] 2. Test Results and Comparative Analysis The performance test results of each embodiment and comparative example are shown in Table 3.
[0081] Table 3 Performance Test Results
[0082]
[0083] The test results in Table 3 clearly show that Examples 1-5 of this application, using the technical solution provided in this application, employ solid lipid nanoparticles as a carrier to encapsulate and deliver active ingredients, thus delaying the oxidative deactivation of the active ingredients. When applied to the skin, upon contact with body temperature and subjected to the frictional pressure of circular application, the framework instantly collapses brittlely, physically disrupting the squalane and glyceryl stearate lattice of the NLC core. The powder spontaneously transforms from a "solid powder" into a highly fluid "nanolipid microfilm," resulting in an extremely smooth and completely non-sticky texture. Simultaneously, the active ingredients detach from the powder's adsorption and penetrate the stratum corneum through lipid structures homologous to the stratum corneum, enhancing the transdermal absorption rate of the active ingredients. Compared to traditional dry powder direct-mixing systems, the skin care powder of this application does not require the active ingredients to be exposed and adsorbed on the powder surface, resulting in excellent storage stability of the finished product without issues such as stratification or localized active ingredient segregation.
[0084] Comparative Examples 1 to 4 illustrate the impact of the choice between solid and liquid lipids on the technical effects of this application. In Comparative Examples 1 and 2, the solid lipids in Example 1 were replaced with stearic acid or cetyl alcohol; in Comparative Examples 3 and 4, the liquid lipids in Example 1 were replaced with caprylic / capric triglyceride or jojoba oil. The lipid mixtures obtained in Comparative Examples 1 and 4 had a melting initiation temperature higher than 38°C, making it difficult for human body surface temperature to trigger the phase transition and softening of the nanolipid carrier, resulting in poor release of active ingredients and thus lacking the function of spontaneous conversion of the dosage form at skin temperature. The lipid mixtures obtained in Comparative Examples 2 and 3 had a melting endpoint lower than 32°C, making the nanolipid carrier prone to softening and agglomeration during room temperature storage, leading to particle size degradation, decreased encapsulation efficiency, and insufficient storage stability. The above results verify the necessity of selecting a specific ratio of glyceryl stearate and squalane to lock the physical softening point of the nanolipid carrier at 32–35°C in this application.
[0085] Comparative Example 5 used nicotinamide as the active ingredient, with a LogP of approximately -0.4, far less than 3.0. Its extremely poor lipophilicity prevented it from being fully co-soluble with glycerol stearate and squalane, making it difficult to encapsulate into the core of the nanolipid carrier. Most of the active ingredient was dispersed in the aqueous phase, resulting in a very low encapsulation rate. It was prone to crystallization during freeze-drying, failing to achieve the body temperature-triggered release effect. Furthermore, slight demulsification and flocculation occurred during preparation, and its storage stability was unsatisfactory under all temperature conditions. Comparative Example 6 used ellagic acid as the active ingredient, with a LogP of approximately 3.5, meeting the lipophilicity requirements and allowing for miscibility with glycerol stearate and squalane. However, it contains multiple acidic phenolic hydroxyl groups, resulting in a pH outside the 5.0–7.0 range. Its introduction into the system significantly lowered the system pH, deviating from the suitable range. The excessively low pH environment promoted the hydrolysis of glycerol stearate, generating free fatty acids that damaged the interfacial membrane of the nanolipid carrier, inducing emulsion flocculation. Simultaneously, the acidic conditions also resulted in poor product stability, with storage stability failing at all temperature conditions. The above results confirm the necessity of limiting the partition coefficient of the active ingredient n-octanol-water and the pH value in this application.
[0086] Comparative Example 7 used Tween 80 as an emulsifier, with an HLB of 15. It could only initially emulsify to form a nanolipid carrier emulsion, failing to construct a sufficiently strong steric barrier. When mixed with a large amount of powder matrix, the emulsifier was easily adsorbed and peeled off by the powder surface, damaging the nanolipid carrier interfacial film. During freeze-drying, it was difficult to resist the mechanical stress caused by ice crystal growth, leading to NLC particle aggregation. Severe demulsification and flocculation occurred during the preparation process, therefore, encapsulation efficiency, spontaneous conversion of the dosage form, and storage stability were not tested. Comparative Example 8 used poloxamer 124, with an apparent HLB of approximately 16, outside the defined range of 20–31. Its low proportion of hydrophilic PEO segments resulted in a weak steric barrier effect. Although the initial emulsion could form a nanolipid carrier, the system had poor resistance to disturbances. During powder mixing and freeze-drying, the nanolipid carriers easily aggregated, failing to maintain a stable dispersion. Severe demulsification and flocculation occurred during the preparation process, therefore, encapsulation efficiency, spontaneous conversion of the dosage form, and storage stability were not tested. The above results verify the necessity of using highly hydrophilic nonionic surfactants with apparent HLB values of 20–31 in this application.
[0087] In Comparative Example 9, the proportion of fluorophlogopite coated with lauroyl lysine was only 35%, which is lower than the 40%–45% range specified in this application. The proportion of modified flake powder was insufficient, resulting in a decrease in the powder's lubrication and dispersion ability. During the mixed NLC emulsion stage, the emulsifier was more easily adsorbed by the powder, increasing the risk of emulsion demulsification. The loose skeleton constructed by the flake-spherical powder became dense, making it difficult to synergistically achieve the softening and release of NLC induced by body temperature and friction. After freeze-drying, the degree of aggregation of the nanolipid carrier increased, and severe demulsification and flocculation occurred during the preparation process. Therefore, the encapsulation rate, spontaneous conversion of the dosage form, and storage stability were not tested. In Comparative Example 10, the porous silica content was only 10%, which is lower than the 15% to 20% range specified in this application. The insufficient porous silica content resulted in a lack of adsorption sites, making it difficult to stabilize during the preparation process. The freeze-drying process lacked effective physical barriers, and the lipid particles were easily damaged. At the same time, the porosity of the spherical three-dimensional framework decreased, and the compaction of the powder matrix increased, which was not conducive to the release of active ingredients. Severe demulsification and flocculation occurred during the preparation process. Therefore, the encapsulation rate, spontaneous conversion of the dosage form, and storage stability were not tested.
[0088] In summary, this application, through precise control of the lipid system of glyceryl stearate and squalane, the n-octanol-water partition coefficient and pH value of the active ingredient, the highly hydrophilic emulsification system with an apparent HLB value of 20-31, the synthesis of a fluorophlogopite and porous silica composite powder skeleton by lauroyl lysine coating, and the complete preparation process, has synergistically solved the technical problems of existing skin care powders, such as easy inactivation of active ingredients, low transdermal penetration, fixed dosage form, and the inability to simultaneously achieve skin feel and efficacy. It has obtained a responsive skin care powder that combines excellent skin feel, long-lasting stability, and high-efficiency skin care activity, and has good industrial application value.
[0089] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the term "comprising" or any other variations thereof is intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes the element.
Claims
1. A method for preparing skin care powder, characterized in that, Includes the following steps: Preparation of active ingredient-loaded nanolipid carrier emulsion: Solid lipids, liquid lipids and active ingredients are heated and melted to obtain an oil phase; an emulsifier and a lyophilization protectant are dissolved in water to obtain an aqueous phase; the oil phase and the aqueous phase are mixed, sheared and emulsified, and then placed in an ice bath for freezing phase change to obtain an active ingredient-loaded nanolipid carrier emulsion; Preparation of wet powder slurry: The nanolipid carrier emulsion loaded with the active ingredient is mixed with the powder matrix and homogenized to obtain a wet powder slurry; Vacuum freeze-drying: The wet slurry of the powder is subjected to vacuum freeze-drying and pulverization to obtain the skin care powder; in, In the oil phase, the solid lipid is glycerol stearate, the liquid lipid is squalane, the active ingredient has an octanol-water partition coefficient LogP greater than or equal to 3.0, and a pH value of 5.0~7.0; and the mass ratio of the solid lipid, the liquid lipid and the active ingredient is (4~8):(15~23):1; The emulsifier is selected from one or more of highly hydrophilic nonionic surfactants with an apparent HLB value of 20 to 31, and the mass of the emulsifier is 0.2 to 0.3 times the total mass of the oil phase. The total mass of the powder matrix is 5 to 7.5 times the total mass of the oil phase. Based on the total mass of the powder matrix, the powder matrix includes 40% to 45% lauroyl lysine-coated synthetic fluorophlogopite and 15% to 20% porous silica.
2. The method for preparing skin care powder according to claim 1, characterized in that, The active ingredients include one or more of astaxanthin, ethyl ferulic acid, psoralen, ascorbyl tetraisopalmitate, β-carotene, tocopherol, retinol, retinyl palmitate, ceramide, phytosterol, and bisabolol.
3. The method for preparing skin care powder according to claim 1, characterized in that, The emulsifier is selected from one or more of poloxamer 188, poloxamer 238, poloxamer 338, and poloxamer 407.
4. The method for preparing skin care powder according to claim 1, characterized in that, The freeze-drying protectant includes trehalose and mannitol, and the mass of the freeze-drying protectant is 0.1 to 0.2 times the total mass of the oil phase.
5. The method for preparing skin care powder according to claim 1, characterized in that, The mass of the water is 1 to 2 times the total mass of the oil phase.
6. The method for preparing skin care powder according to claim 1, characterized in that, The powder matrix also includes one or more of the following: unmodified synthetic fluorophlogopite, starch derivatives, boron nitride, inorganic functional composite powder, silica powder, metal oxide powder, inorganic phosphate powder, organosilicon resin microspheres, and organic polymer microspheres.
7. The method for preparing skin care powder according to claim 1, characterized in that, In the step of preparing the nanolipid carrier emulsion loaded with active ingredients, the shearing speed of the shear emulsification is 10,000 rpm to 14,000 rpm, and the time is 4 to 6 minutes.
8. The method for preparing skin care powder according to claim 1, characterized in that, The step of preparing the powder wet slurry is carried out at 10~15℃; and / or, before vacuum freeze-drying the powder wet slurry, the powder wet slurry is pre-frozen at -50℃~-40℃ for 2 hours to 4 hours.
9. A skin care powder, characterized in that, Prepared according to the method described in any one of claims 1 to 8.
10. The use of the skin care powder according to claim 9 in the preparation of powder cosmetics.